Comparative analysis of the institute of chaplainty - Holiachenko, Ivan (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
This article provides a comparative analysis of the institution of chaplaincy. France’s experience with the public movement under the auspices of chaplaincy, as well as the development of partnerships with religious organizations in order to provide greater spiritual support for military personnel, is interesting and necessary, which is expressed in the development of joint programs and projects aimed at ensuring religious freedom and supporting the spiritual health of military personnel. . The author noted that the US experience in cooperation with other services of the military organization is important and necessary. Today, it is necessary to introduce systematic interaction between the chaplaincy service and psychological and medical services in order to provide comprehensive support to military personnel. It is also proposed to provide for the responsibility of military chaplains for violating the norms that regulate the institution of chaplaincy and types of responsibility, as well as to introduce the possibility of a separate military chaplain for the leadership positions of the General Staff of Ukraine. It is noted that the NATO alliance pays special attention to the institute of chaplaincy. To obtain the status of a NATO chaplain, it is necessary to undergo special training. The purpose of this training course is to educate military chaplains in NATO standards and address issues related to the ability to perform joint ministry and religious advisory duties during military operations. This involves the study of international law, ethics and psychological methods to support commanders and personnel in their missions. Using the example of the international experience of the chaplaincy of the Republic of Poland, it was noted that the Polish state equated the status of chaplains with the status of professional soldiers: in the army, they receive officer ranks and salaries. In the military, chaplains not only meet the religious needs of soldiers, but also prevent mental trauma among those who experience fatigue and stress.